EFFECT OF WORK ENVIRONMENT, WORK DISCIPLINE AND WORK SANCTIONS ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION IN PT. PERTAMINA IN BATAM CITY - Handoko Gotama, William; Wibisono, Chablullah; Gita Indrawan, Mohamad; Khaddafi, Muammar (RADJA PUBLIKA, 2022)
This study aims to determine the effect of work environment, work discipline and work sanctions on employee performance through job satisfaction at PT. Pertamina in Batam City. This study uses primary and secondary data obtained through respondents, where respondents will provide verbal responses and or written responses in response to the statements given. The data analysis method used is the questionnaire method, namely by providing a list of questions or questionnaires to the respondents. The results show that Work Discipline has a positive path coefficient value of 0.152 and a T-Statistics value of 1.695 <1.96 (not significant), Work Discipline has a positive path coefficient value of 0.198 and a T-Statistics value of 3.176> 1.96 (significant). , Job Satisfaction has a positive path coefficient value of 0.514 and a T-Statistics value of 5.062> 1.96 (significant), Work Environment has a positive path coefficient value of 0.139 and a T-Statistics value of 1.850 <1.96 (not significant), Work Environment has a positive path coefficient value of 0.197 and a T-Statistics value of 2.833> 1.96 (significant), Work Sanctions have a positive path coefficient value of 0.674 and a T-Statistics value of 8.257> 1.96 (significant), Work Sanctions have a path coefficient value positive value of 0.117 and the value of T-Statistics 0.934 <1.96 (not significant), Work Discipline (X2) -> Job Satisfaction (Y) -> Employee Performance (Z) is 0.078 (positive) with a probability value of 1.61 9 > 0.05 (not significant), Work Environment (X1) -> Job Satisfaction (Y) -> Employee Performance (Z) is 0.072 (positive) with a probability value of 1.756 > 0.05 (not significant), Sanctions Work (X3) -> Job Satisfaction (Y) -> Employee Performance (Z) is 0.347 (positive) with a probability value of 4.402 > 0.05 (not significant).